2018
DOI: 10.1302/0301-620x.100b1.bjj-2017-1065.r1
|View full text |Cite|
|
Sign up to set email alerts
|

The risk of cardiac failure following metal-on-metal hip arthroplasty

Abstract: AimsThe aim of this study was to determine whether patients with metal-on-metal (MoM) arthroplasties of the hip have an increased risk of cardiac failure compared with those with alternative types of arthroplasties (non-MoM). Patients and Methods ConclusionThe risk of cardiac failure following total hip arthroplasty was not increased in those in whom MoM implants were used, compared with those in whom other types of prostheses were used, in the first seven years after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 34 publications
1
21
0
1
Order By: Relevance
“…What should we as cardiologists take from this work? As with several other clinical/ large-scaIe population studies, [4][5][6] this work failed to detect a strong signal for heart failure risk with MoM hips. Indeed one study from the largest joint registry (including data from greater than 500,000 patients) suggested lower heart failure risk in MoM patients.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…What should we as cardiologists take from this work? As with several other clinical/ large-scaIe population studies, [4][5][6] this work failed to detect a strong signal for heart failure risk with MoM hips. Indeed one study from the largest joint registry (including data from greater than 500,000 patients) suggested lower heart failure risk in MoM patients.…”
supporting
confidence: 63%
“…Indeed one study from the largest joint registry (including data from greater than 500,000 patients) suggested lower heart failure risk in MoM patients. [5] One smaller epidemiological study found potentially higher risks of heart failure but only in a small subgroup of elderly men with one particular high risk prosthesis. [7] Currently, there is no evidence to advise routine cardiac screening of MoM patients and we think that patients should be reassured unless their blood levels are very high.…”
mentioning
confidence: 99%
“…However, a larger study using National Joint Registry (NJR) data from England and Wales demonstrated that MoMHA patients were not at increased risk of heart failure compared with non-MoMHA patients (Sabah et al. 2018 ), with the same authors reporting that MoMHA patients with high blood metal ion concentrations undergoing comprehensive cardiac investigations had no detectable heart pathology (Berber et al. 2017 ).…”
Section: Threshold For Armd Revision Surgerymentioning
confidence: 99%
“…This more intensive follow-up may reflect the MHRA’s continued and serious concerns about the long-term systemic effects of ions released from MoM hip replacements, which are largely unknown [ 11 , 12 ]. Other large cohort studies have shown no association between MoM hip replacements and the risk of cardiac disease in the medium term, another potential deleterious effect of metal ion release [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%